3, 5‐diiodothyronine (3, 5‐T2) reduces blood glucose independently of insulin sensitization in obese mice. (17th November 2016) - da Silva Teixeira, S.; Filgueira, C.; Sieglaff, D. H.; Benod, C.; Villagomez, R.; Minze, L. J.; Zhang, A.; Webb, P.; Nunes, M. T.
Abstract: Aim: Thyroid hormones regulate metabolic response. While triiodothyronine (T3) is usually considered to be the active form of thyroid hormone, one form of diiodothyronine (3, 5‐T2) exerts T3‐like effects on energy consumption and lipid metabolism. 3, 5‐T2 also improves glucose tolerance in rats and 3, 5‐T2 levels correlate with fasting glucose in humans. Presently, however, little is known about mechanisms of 3, 5‐T2 effects on glucose metabolism. Here, we set out to compare effects of T3, 3, 5‐T2 and another form of T2 (3, 3‐T2) in a mouse model of diet‐induced obesity and determined effects of T3 and 3, 5‐T2 on markers of classical insulin sensitization to understand how diiodothyronines influence blood glucose. Methods: Cell‐ and protein‐based assays of thyroid hormone action. Assays of metabolic parameters in mice. Analysis of transcript and protein levels in different tissues by qRT‐PCR and Western blot. Results: T3 and 3, 5‐T2 both reduce body weight, adiposity and body temperature despite increased food intake. 3, 3′‐T2 lacks these effects. T3 and 3, 5‐T2 reduce blood glucose levels, whereas 3, 3′‐T2 worsens glucose tolerance. Neither T3 nor 3, 5‐T2 affects markers of insulin sensitization in skeletal muscle or white adipose tissue (WAT), but both reduce hepatic GLUT2 glucose transporter levels and glucose output. T3 and 3, 5‐T2 also induce expression of mitochondrial uncoupling proteins (UCPs) 3 and 1 in skeletal muscle and WAT respectively. Conclusions: 3, 5‐T2 influences glucose metabolism in a manner that is distinct from insulin sensitization and involves reductions in hepatic glucose output and changes in energy utilization.